Subject-Specific Geometry of FE Lumbar Spine Models for the Replication of Fracture Locations Using Dynamic Drop Tests - Rieger, Laura K.; Shah, Alok; Schick, Sylvia; Draper, Dustin B.; Cutlan, Rachel; Peldschus, Steffen; Stemper, Brian D. (Annals of biomedical engineering, 2024)
For traumatic lumbar spine injuries, the mechanisms and influence of anthropometrical variation are not yet fully understood under dynamic loading. Our objective was to evaluate whether geometrically subject-specific explicit finite element (FE) lumbar spine models based on state-of-the-art clinical CT data combined with general material properties from the literature could replicate the experimental responses and the fracture locations via a dynamic drop tower-test setup. The experimental CT datasets from a dynamic drop tower-test setup were used to create anatomical details of four lumbar spine models (T12 to L5). The soft tissues from THUMS v4.1 were integrated by morphing. Each model was simulated with the corresponding loading and boundary conditions from the dynamic lumbar spine tests that produced differing injuries and injury locations. The simulations resulted in force, moment, and kinematic responses that effectively matched the experimental data. The pressure distribution within the models was used to compare the fracture occurrence and location. The spinal levels that sustained vertebral body fracture in the experiment showed higher simulation pressure values in the anterior elements than those in the levels that did not fracture in the reference experiments. Similarly, the spinal levels that sustained posterior element fracture in the experiments showed higher simulation pressure values in the vertebral posterior structures compared to those in the levels that did not sustain fracture. Our study showed that the incorporation of the spinal geometry and orientation could be used to replicate the fracture type and location under dynamic loading. Our results provided an understanding of the lumbar injury mechanisms and knowledge on the load thresholds that could be used for injury prediction with explicit FE lumbar spine models.